Energy poverty, its intensity and health in vulnerable populations in a Southern European city - Juli Carrere; Andrés Peralta; Laura Oliveras; María José López; Marc Marí-Dell'Olmo; Joan Benach; Ana M. Novoa (Elsevier, 2021)
Objective: To describe and compare the health status between vulnerable population participating in a program to tackle energy poverty (Energía, la justa) and the non-energy poor Barcelona (Spain) population and to analyse among participants the effect of energy poverty intensity on health. Method: Cross-sectional study based on data from program participants obtained before the intervention. Participants (1799 women and 671 men) were compared to non-energy poor population of Barcelona (1393 women and 1215 men) sampled from the Barcelona Public Health Survey (2016). Standardized prevalence and prevalence ratios of self-perceived poor health, asthma, chronic bronchitis, and depression and/or anxiety were estimated, and among participants the association between health status and energy poverty intensity was estimated with multivariate models. Results: The probability of poor self-perceived physical and mental health ranged from 2.2 to 5.3 times greater in the program participants than non-energy poor Barcelona population. Among program participants, those most affected were found to be the most likely to report poor health outcomes, regardless of other sociodemographic factors. Conclusions: The prevalence of poor physical and mental health was considerably higher among women and men participating in the programme compared to the non-energy poor population and was even worse among those who were more severely affected. Public policies that tackle energy poverty and its consequences are urgently needed in Spain. Resumen: Objetivo: Describir y comparar el estado de salud entre la población vulnerable que participa en un programa de lucha contra la pobreza energética (Energía, la justa) y la población sin pobreza energética de Barcelona (España), y analizar entre las personas participantes el efecto de la intensidad de la pobreza energética en la salud. Método: Estudio transversal basado en datos de los/las participantes en el programa obtenidos antes de la intervención. Se compararon los/las participantes (1799 mujeres y 671 hombres) con población sin pobreza energética de Barcelona (1393 mujeres y 1215 hombres) seleccionada de la Encuesta de Salud Pública de Barcelona (2016). Se estimaron la prevalencia estandarizada y las razones de prevalencia de mala salud, asma, bronquitis crónica y depresión o ansiedad autopercibida. Entre los/las participantes se estimó la asociación entre el estado de salud y la intensidad de la pobreza energética con modelos multivariantes. Resultados: Los/las participantes presentaron entre 2,2 y 5,3 veces peores resultados en salud que la población sin pobreza energética. Entre los/las participantes se encontró que las personas más afectadas eran las que tenían más probabilidades de reportar peores resultados de salud, independientemente de otros factores sociodemográficos. Conclusiones: La prevalencia de mala salud física y mental era considerablemente mayor en las mujeres y los hombres que participaron en el programa en comparación con la población sin pobreza energética, y era aún peor entre los/las más severamente afectados. En España se necesitan con urgencia políticas públicas que aborden la pobreza energética y sus consecuencias.